Sydromic management of sexually transmitted diseases at primary health care level in Tanzania - Mayaud, Phillipe; Mwijarubi, Ezra; Gavyole, Awene (Brazilian Journal of Sexually Transmitted Diseases, 1998)
The HIV epidemie has been increasing in severiry in many pares of sub Saharan Africa, aduh prevalence exceeding 20% in some urban centres, wirh lower but steadily increasing prevalence in rural areas where the majorlcy of Africans tive. SeveraL studies have suggesced chat the sexual rransmission of HTV may be considerably enhanced in the presence of other STDs which are highly prevalent in many pares of Africa, due at least partly to the poor quality of STD treatmenc services. The WHO therefore has been promocingimprovemem of STD services in order to reduce che prevalence ofSTOs in the popularion, rhereby reducing che cra.nsmission of HIV. Measuremenc of the impacr, feasibility and cosreffecciveness of such a programme has been provided in a randomised-communit triai conducced in the Mwanza Region of Tanzania.Syndromic managemem of STDs was well accepced by staff and patients. Management was effective in curing symptomaric STD patients and superior to formerly prevailing rrearment praccices. Successful implementation depended crucially on qualiry craining and supervision of health workers and on the regular su pply of drugs.